(untitled) (Journal of the College of Basic Education, 2023)
Values are considered the basis for the stability of nations because they are the basic control and standard for the behavior of individuals and groups. They are also of great importance in the educational process, especially when these values are based on a solid and strong reference in their sources and purposes by linking them to the Islamic reference derived from the revelation of “God” and the Sunnah of His Noble Prophet, “Muhammad.” “The interest in raising a Muslim child is, in fact, the interest in the future of the Islamic nation and its cultural and intellectual heritage. It is evident in the fact that the research deals with a phenomenon of the era that is constantly evolving day after day, namely modern means of communication. The reason for my choosing this topic is due to Many of the children of the Islamic nation lack an Islamic educational curriculum based on the commands of God and following the Sunnah of His Prophet Muhammad, may God bless him and grant him peace, and the importance of the childhood stage in instilling faith, worship, knowledge, health, and other things in the child, so I wanted to delve into this field. The research generally aims to outline the features of the protective role of the Muslim family. In protecting children from the negative effects of electronic means of communication. In this modest research, I followed the descriptive approach, using the methods of deduction and induction. After the introduction, I divided my modest research into two sections, as follows: The first section: Islamic values and raising children, and it contains three demands: The first topic The second topic: The concept of the values of Islamic education. The second topic: Characteristics of the values of Islamic education. The third topic: Raising a child in Islam. The second topic: The effects of the use of modern technologies on the child. It included two requirements: The first requirement: The negative effects of using the Internet on the child. The second topic is the preventive role of the Muslim family in Child protection through the directives of the Holy Qur’an and the purified Sunnah of the Prophet, then the conclusion, which included the most important results of the research, and finally the sources and references.